Controle de Bambusa tuldoides munro e seus efeitos na chuva de sementes em floresta estacional semidecidual - Camargo, Betina (2020)
The bamboo dominance in forest remnants can cause disturbances in the ecological succession mechanisms (light, temperature, humidity, etc.). When not managed, bamboo species can become persistent for long periods. Still, studies on methods of control bamboo dominance are scarce. The present work aimed to understand how different methods of bamboo control affect the structure and composition of the seed rain. The study was carried out in the municipality of Eldorado do Sul, Rio Grande do Sul, covering four areas of riparian forests, three of which the exotic bamboo-dominate Bambusa tuldoides Munro and one bamboo-free, they are: chemical control of bamboo (CQ), mechanical control of bamboo (CM), no control bamboo (BT), and a remnant of Seasonal Semideciduous Forest (FESD) bamboo-free. The seed rain was evaluated during 24 months (Jul / 2015 to Jun / 2017), in 10 seed traps 1m² in each area, totaling 40 seed traps, the collections of the material deposited in these collectors were carried out quarterly. The seeds were classified into morphospecies, according to their external morphology and accounted for. The areas were compared in terms of richness, abundance, diversity, equability, seed dispersal mechanisms and floristic composition of the seed rain. Significant differences were found in the structure and composition of the seed rain between the bamboo control areas, comparing with the reference area (FESD) and no control bamboo (BT). BT showed an abundance of seed rain statistically lower than the other areas. CQ showed a greater total abundance, due to the overabundance of a morphospecies (Mikania sp.), However, the species richness was low and did not differ from BT. In addition, CQ showed low input of seeds with biotic dispersion, differing statistically from FESD. CM presented abundance of seeds dispersed by biotic means similar to the reference area (FESD). The mechanical control of bamboo (CM) proved to be an effective method for the return and quality of seed rain. It is concluded that the mechanical control of bamboo is efficient to promote the return of seed rain. The chemical control of bamboo does not favor the richness of species, possibly, it needs more time of monitoring so that more expressive results can be evidenced.